Investigating tectonic links between the deep Volturno plain and Campanian volcanism using vintage seismic and potential field data - Pier Paolo G. Bruno; Maria Luisa Putignano; Federico Cella; Giovanni Florio (Scientific Reports)
Abstract This study investigates the tectonic and subsurface structure of the Volturno Plain, a region linking the Southern Apennines with active volcanic districts of Campania. Vintage seismic profiles were vectorized, depth-converted, and integrated with historical gravity and magnetic data. The analysis reveals a coastal half-graben structure primarily controlled by NE-trending normal faults, with NW-trending faults that downthrow the carbonate outcrops of the Southern Apennines toward the coast. These fault systems collectively drive subsidence exceeding 5 km beneath the mouth of the Volturno River. Enhanced Horizontal Derivative analysis of gravity data extends fault traces beyond the seismic coverage and helps to characterize major NE-striking fault systems, such as the Mt. Massico and Villa Literno fault zones, which are likely active and exhibit aseismic creep or low-magnitude seismicity. Gravity and magnetic anomalies highlight variations in the thickness of the sedimentary cover within fault-controlled depressions, as well as the presence of volcanic deposits in the southern plain, associated with buried volcanic edifices whose emplacement was influenced by NE- and NW-trending faults. InSAR-derived surface deformation patterns show a partial alignment with these fault systems but also reflect non-tectonic factors such as sediment compaction and anthropogenic activities. Our findings confirm the structural control of NE-trending faults on the plain’s evolution and Campanian volcanism. This work fills a knowledge gap regarding the tectonic and structural setting of the carbonate basement in the northern part of the Campanian Plain, for which a map of the depth to the base of the post-Miocene sedimentary cover was not yet available. This paper also highlights the value of integrating legacy seismic and potential field data using modern techniques to unravel the interplay of tectonic and magmatic processes.